Directors of emergency medicine's beliefs about, barriers to, and enablers of solutions to emergency department crowding and access block. (20th May 2020) - Rixon, Andrew; Wilson, Samuel; Judkins, Simon; White, Peter
Abstract: Objective: To identify opportunities for directors of emergency medicine (DEMs) to lead change efforts to address ED crowding and access block. Methods: DEMs were surveyed about their beliefs about, barriers to, and enablers of solutions to ED crowding and access block. Results: Key barriers were insufficient resources, entrenched hospital culture, and lack of political will to address ED crowding and access block. Key enablers were developing hospital‐wide understanding of the problems, developing a supportive hospital culture, and improved engagement by hospital executive. Conclusion: Addressing the political and cultural forces that sustain ED crowding and access block are key adaptive challenges requiring DEM leadership.